Teachers’ and Students’ Understanding of the Course Syllabus - Mammadova, Turan; Huseynli, Madina; Aliyeva, Tajlibayim (ADA University, 2023)
The course syllabus is a document that contains every necessary information. It includes a list of the subjects you will cover as well as the deadlines for any homework assignments, such as tests, quizzes, or examinations. While syllabi can help students feel engaged and provide a productive learning environment, debates about their usefulness are seldom found. In light of recent studies and theories on syllabi, for this Capstone project our aim was to find the perceptions of instructors and students about syllabi in higher education settings in Baku. The researchers employed interviews to identify the instructors’ and students’ definitions of the syllabus, instructors’ experiences of designing the course syllabus, and students’ suggestions and expectations of the course syllabus. According to the findings of this study, teachers often utilize the syllabus as a framework to decide what to accomplish and teach. Despite being aware of the several kinds of syllabi, most of them were unable to identify which kind it was. Findings indicate that students use the course syllabus to learn about the subject matter of the lectures and the test dates, which also serve as a course map. The majority of students were unaware of the course objectives and expectations, despite some professors emphasizing their relevance. As a result, as a Capstone team, we chose to create training for teachers. One of Baku's higher education institutes will host the workshop. This workshop's major objective is to increase public knowledge of the value of the course syllabus in the process of teaching and learning. The objective, advantages, and methods for involving students in using the course syllabus will be explained to instructors.
Keywords: Curriculum planning -- Higher education; College teaching -- Methodology; Teacher-student relationships -- Azerbaijan; Education